Transgenic mouse model of cutaneous adnexal tumors - Yusuke Kito; Chiemi Saigo; Kurabayashi Atsushi; Furihata Mutsuo; Takeuchi Tamotsu (The Company of Biologists, 2014)
TMEM207 was first characterized as being an important molecule for the invasion activity of gastric signet-ring cell carcinoma cells. In order to unravel the pathological properties of TMEM207, we generated several transgenic mouse lines, designated C57BL/6-Tg (ITF-TMEM207), in which murine TMEM207 was ectopically expressed under a truncated (by ~200 bp) proximal promoter of the murine intestinal trefoil factor (ITF) gene (also known as Tff3). Unexpectedly, a C57BL/6-Tg (ITF-TMEM207) mouse line exhibited a high incidence of spontaneous intradermal tumors with histopathological features that resembled those of various human cutaneous adnexal tumors. These tumors were found in ~14% female and 13% of male 6- to 12-month-old mice. TMEM207 immunoreactivity was found in hair follicle bulge cells in non-tumorous skin, as well as in cutaneous adnexal tumors of the transgenic mouse. The ITF-TMEM207 construct in this line appeared to be inserted to a major satellite repeat sequence at chromosome 2, in which no definite coding molecule was found. In addition, we also observed cutaneous adnexal tumors in three other C57BL/6-Tg (ITF-TMEM207) transgenic mouse lines. We believe that the C57BL/6-Tg (ITF-TMEM207) mouse might be a useful model to understand human cutaneous adnexal tumors.